Initial experience with the treatment of concomitant aortic pseudoaneurysm and thoracolumbar spinal fracture: Case report. (December 2017) - Kovari, Viktor Zsolt; Pecsi, Ferenc; Cs.Janvari, Mate; Veres, Robert
Abstract: One blunt abdominal aortic disruption (BAAD) and one blunt thoracic aortic injury (BTAI) case are presented. Both aortic injuries were combined with spinal fractures. In the BAAD case the aortic pseudoaneurysm manifested just above the lumbar fracture while in the BTAI case the aortic injury appeared several vertebras below the thoracal fracture site, suggesting different mechanisms in the aortic wall damage. In both cases the aortic wall first was sealed, successfully, by endovascularly-placed stents, meaning the risks of open aortic reconstructive surgery could be avoided. The adjacent crucial vessel's preservation, despite the stent covering the left subclavian artery and the left common carotid artery in one of the cases was verified by post-operative computed tomography angiography (CTA) examination. In second stage those spinal fractures which were deemed unstable were stabilized by the fixateur interne (a transpedicular screw-rod system). With this treatment sequence we wanted to avoid the unnecessary risk of a possible rupture of the unsealed aortic wall during positioning for the spinal procedure and during the spinal surgery. Both patients recovered from their aortic and spinal injuries.